Magnetic Maze Games to Strengthen Concentration Skills in Early Learners: Permainan Labirin Magnetik untuk Meningkatkan Kemampuan Konsentrasi pada Anak Usia Dini - Kifayah, Sayyidatul; Rocmah, Luluk Iffatur (Indonesian Journal of Education Methods Development, 2025)
Background: Early childhood learners often exhibit low concentration levels, requiring engaging and developmentally appropriate learning media. Specific Background: At TK Islam Al-Irsyad, only 35% of children demonstrated adequate concentration during routine classroom activities. Knowledge Gap: Previous studies explored maze games but rarely implemented multi-themed magnetic maze media integrated into a smart-box system. Aim: This study aims to strengthen concentration skills of children aged 4–5 years through magnetic maze educational games. Methods: A Classroom Action Research design using Kemmis and McTaggart’s model was conducted in two cycles, involving 15 children. Data were collected through observation, interviews, and documentation. Results: Improvements were observed across four indicators: problem solving, focus, memory retention, and hand–eye coordination. Concentration completeness increased from 35% (pre-cycle) to 62% (Cycle I) and 90% (Cycle II). Novelty: The study introduces four themed magnetic maze activities integrated into a smart-box, supported by preparatory ice-breaking tasks to activate children’s readiness. Implications: Magnetic maze games offer an interactive approach that enhances cognitive engagement and can be adopted as an effective concentration-building medium in early childhood settings. Highlights• Children’s concentration improved across two action cycles• Multi-themed magnetic maze promotes cognitive engagement• Smart-box design supports structured and playful learning Keywords: Concentration, Magnetic Maze, Early Childhood, Educational Games, Classroom Action Research